Diversity of endophytic bacteria of Dendrobium officinale based on culture-dependent and culture-independent methods. Issue 1 (2nd January 2017) - Pei, Cong; Mi, Chunyi; Sun, Lihua; Liu, Wenhong; Li, Ou; Hu, Xiufang
ABSTRACT: Culture-dependent and culture-independent methods were compared and evaluated in the study of the endophytic diversity of Dendrobium officinale . Culture-independent methods consisted of polymerase chain reaction–denaturing gradient gel electrophoresis (PCR-DGGE) and metagenome methods. According to the results, differences were found between the three methods. Three phyla, namely Firmicutes, Proteobacteria, and Actinobacteria, were detected using the culture-dependent method, and two phyla, Firmicutes and Proteobacteria, were detected by the DGGE method. Using the metagenome method, four major phyla were determined, including Proteobacteria (76.54%), Actinobacteria (18.56%), Firmicutes (2.27%), and Bacteroidetes (1.56%). A distinct trend was obtained at the genus level in terms of the method and the corresponding number of genera determined. There were 449 genera and 16 genera obtained from the metagenome and DGGE methods, respectively, and only 7 genera were obtained through the culture-dependent method. By comparison, all the genera from the culture-dependent and DGGE methods were contained in the members determined using the metagenome method. Overall, culture-dependent methods are limited to 'finding' endophytic bacteria in plants. DGGE is an alternative to investigating primary diversity patterns; however, the metagenome method is still the best choice for determining the endophytic profile in plants. It is essential to use multiphasic approaches to study cultured and uncultured microbes.